Pemanfaatan Pelepah Sawit dan Kotoran Ayam Ras untuk Pembuatan Pupuk Bokashi pada Kelompok Wanita Tani Padang Baru Babatan, Seluma, Bengkulu - Nurlianti Nurlianti; Prihanani Prihanani (Abdihaz: Jurnal Ilmiah Pengabdian pada Masyarakat, 2021)
The Utilization of Oil Palm Midrib-leaf and Chicken Manure for Making Bokashi Fertilizer in the Women's Farmers Group Padang Baru Babatan, Seluma, Bengkulu The purpose of the community service program is to utilize agricultural waste, namely oil palm midrib-leaf and chicken manure which are often found in this Babatan Village, Sukaraja Subdistrict, Seluma Regency, Bengkulu. In addition, this program was aimed to increase knowledge and skill to produce bokashi fertilizer with raw materials found around them. The methods used were lecture, demonstration plots, and mentoring. The results of the activity were the increasing of family income by making bokashi utilizing waste raw materials around their lives, namely bokashi made from palm fronds and broiler chicken waste that is ready to be sold. In limited quantities, they have been able to sell their products to meet the needs of other farmer groups or the general public in need.